Prostate cancer: the nurse’s performance in primary health care - Macena, Luiz Felipe da Costa; Alencar Neta, Raimunda Leite de; Silva, Francisca Mayara Gabriel da; Feitosa, Ankilma do Nascimento Andrade; Quental, Ocilma Barros de; Medeiros, Renata Lívia Silva Fonseca Moreira de (Brazilian Journal of Production Engineering, 2023)
The National Cancer Institute (INCA) states that prostate cancer is one of the most common among men, second only to non-melanoma skin cancer. The nurse plays one of the most important roles in the Family Health Strategy (ESF), understanding the principles and guidelines that govern primary care, according to the National Primary Care Policy (PNAB). The objective is to analyze the performance of the primary health care team in the face of prostate cancer. This is an integrative literature review study, which was carried out, through a data survey, in the scientific bases: LILACS, SCIELO and BDENF available in the VHL. Based on the applicability of the defined eligibility criteria, seven studies were selected to compose the results sample. Results and Discussions: It was found that one of the factors that influence men’s resistance to the health service may be directly related to the lack of knowledge of the public policy (PNAISH), health service opening hours and rights. Conclusion: It was evident that there is male evasion in health services, due to the male stereotype, allowing us to demonstrate that difficulties exist, although there are paths that can be traced to reverse this scenario.